Analysis of the Study Asbabun Nuzul: “The Urgency and Contribution in Understanding the Qur’an.” - Mukhlis, Mukhlis (Sekolah Tinggi Ilmu Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This research aims to know the analysis of the urgency and contribution of the study on Asbabun Nuzul in understanding the Quran. Asbabun Nuzul, or the reasons for the revelation of the verses of the Quran, plays a crucial role in the context of interpreting and understanding the sacred verses. The research employs the method of literature or library research, conducted by gathering information from existing sources such as books, journals, articles, and other publications related to the research topic. In this study, the author explores how understanding the historical and situational context of the verses of the Quran can enrich interpretation and its application in daily life. Through an analytical approach, the author highlights the urgency of studying Asbabun Nuzul to avoid errors and misunderstandings in interpreting the verses of the Quran. Based on the research findings, it is revealed that understanding Asbabun Nuzul is essential for comprehending the verses and avoiding misinterpretations. It helps to specify laws based on the reasons for revelation and provides clarity to the verses. The findings of this study are expected to contribute to the development of more holistic and contextual methods of interpreting the Quran, enriching the understanding of the Muslim community towards the Quran.